Implementation and role of modern musculoskeletal imaging in rheumatological practice in member countries of EULAR. Issue 2 (25th June 2019) - Mandl, Peter; Ciechomska, Anna; Terslev, L; Baraliakos, Xenofon; Conaghan, PG; D'Agostino, Maria Antonietta; Iagnocco, Annamaria; van der Laken, Conny J; Ostergaard, Mikkel; Naredo, E
Abstract : Objectives: To document the current training, implementation and role of modern musculoskeletal imaging techniques: ultrasound, magnetic resonance imaging, computed tomography and positron emission tomography, among rheumatologists in the member countries of the EULAR. Methods: English-language questionnaires for each imaging modality developed by a EULAR task force were sent out to national and international scientific societies as well as imaging experts in the given modalities involved in research and/or training. The surveys were distributed via an online survey tool (SurveyMonkey). Simple descriptive and summary statistics were calculated from the responses. Results: More than 90% of ultrasound (US) experts reported the availability of a US unit in their department. Suspicion of rheumatoid arthritis and spondyloarthritides were the main clinical indications for performing US for diagnostic purposes. Suspicion of sacroiliitis and degenerative spine disease were the most common indications to perform magnetic resonance imaging (MRI) or computed tomography (CT) for diagnostic purposes, while positron emission tomography was mainly performed to diagnose large vessel vasculitis and to investigate fever of unknown origin. The reported percentage of rheumatologists performing US was highly variable, ranging from more than 80% in 6% of countries to less than 10% in 15% of countries. The majority of experts (77%) reported that their national rheumatology societies organise musculoskeletal US courses, while courses in MRI or CT organised by the national rheumatology societies were less commonly reported (29% and 8%, respectively). Conclusions: Rheumatologists in Europe utilise modern imaging techniques; however, access to the techniques and training offered is varied.